Discrete element modeling of indentation tests to investigate mechanisms of CO2‐related chemomechanical rock alteration. Issue 11 (12th November 2016) - Sun, Zhuang; Espinoza, D. Nicolas; Balhoff, Matthew T.
Abstract: During CO2 injection into geological formations, petrophysical and geomechanical properties of host formations can be altered due to mineral dissolution and precipitation. Field and laboratory results have shown that sandstone and siltstone can be altered by CO2 ‐water mixtures, but few quantitative studies have been performed to fully investigate underlying mechanisms. Based on the hypothesis that CO2 ‐water mixtures alter the integrity of rock structure by attacking cements rather than grains, we attempt to explain the degradation of cementation due to long‐term contact with CO2 and water and mechanisms for changes in rock mechanical properties. Many sandstones, including calcite‐cemented quartzitic sandstone, chlorite‐cemented quartzitic sandstone, and hematite‐cemented quartzitic sandstone, contain interparticle cements that are more readily affected by CO2 ‐water mixtures than grains. A model that couples the discrete element method and the bonded‐particle model is used to perform simulations of indentation tests on synthetic rocks with crystal and random packings. The model is verified against the analytical cavity expansion model and validated against laboratory indentation tests on Entrada sandstone with and without CO2 alteration. Sensitivity analysis is performed for cementation microscopic parameters including stiffness, size, axial, and shear strength. The simulation results indicate that the CO2 ‐related degradation of mechanical properties in bleached Entrada sandstone can be attributed to the reduction of cement size rather than cement strength. Our study indicates that it is possible to describe the CO2 ‐related rock alteration through particle‐scale mechanisms. Key Points: The bonded‐particle model successfully models indentation on cemented sandstones CO2 ‐related mechanical rock degradation in bleached Entrada sandstone can be ascribed to the degradation of interparticle cementation CO2 ‐related degradation on cement bonds is likely due to the reduction of cement size rather than cement strength